Spectroscopy of neutron-rich scandium isotopes. (May 2020) - Koseoglou, P.; Werner, V.; Pietralla, N.; Söderström, P.-A.; Doornenbal, P.; Obertelli, A.; Achouri, N.; Baba, H.; Browne, F.; Calvet, D.; Château, F.; Chen, S.; et al.
Abstract: Within the SEASTAR III campaign at the Radioactive Isotope Beam Factory, at the RIKEN Nishina Center, neutron-rich isotopes in the vicinity of 53 K were produced from the fragmentation of the primary 70 Zn beam on a 9 Be target. After nucleon knockout reactions on the secondary liquid hydrogen MINOS target the known γ rays of the neutron-rich 55 Sc isotope were observed (shown in this proceedings) and γ rays from 57, 59 Sc isotopes have been identified for the first time. The evolution of the occupied nucleon orbitals of these nuclei in the ground and excited state is investigated under the prism of the tensor force.